2016
DOI: 10.1128/jvi.00163-16
|View full text |Cite
|
Sign up to set email alerts
|

Reversion of Cold-Adapted Live Attenuated Influenza Vaccine into a Pathogenic Virus

Abstract: The only licensed live attenuated influenza A virus vaccines (LAIVs) in the United States (FluMist) are created using internal protein-coding gene segments from the cold-adapted temperature-sensitive master donor virus A/Ann Arbor/6/1960 and HA/NA gene segments from circulating viruses. During serial passage of A/Ann Arbor/6/1960 at low temperatures to select the desired attenuating phenotypes, multiple cold-adaptive mutations and temperature-sensitive mutations arose. A substantial amount of scientific and cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 54 publications
1
45
0
2
Order By: Relevance
“…The current MDV A/AA/6/60 LAIV has mutations mainly located in areas of the polymerase complex. There is always a concern that, with enough pressure, the MDV A/AA/6/60 LAIV could introduce mutations to compensate and revert back to a pathogenic strain [47]. By introducing mutations into additional viral genes (PA and NS1), the probability of reversion to a more virulent strain is decreased even further, adding to the increased safety profile desired for an MDV LAIV.…”
Section: Discussionmentioning
confidence: 99%
“…The current MDV A/AA/6/60 LAIV has mutations mainly located in areas of the polymerase complex. There is always a concern that, with enough pressure, the MDV A/AA/6/60 LAIV could introduce mutations to compensate and revert back to a pathogenic strain [47]. By introducing mutations into additional viral genes (PA and NS1), the probability of reversion to a more virulent strain is decreased even further, adding to the increased safety profile desired for an MDV LAIV.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have shown that LAIV can induce a cross-protective response against both homogenous and heterologous viruses challenge [7,35]. TS IAV is safe and effective, and can induce humoral, mucosal and cellular immunity which can protect humans from influenza virus infection [23,36,37]. The results in our study also found that 192t-6, 192t-9 and TS IAV could protect mice from PR8 homologous virus infection and reduce the replication of influenza virus in mice, and 192t-6 and 192t-9 had similar protective effects on mice as TS IAV.…”
Section: Discussionmentioning
confidence: 99%
“…We next determined the virulence of miR-192 targeted viruses in vivo. Meanwhile, a temperature-sensitive (TS IAV) constructed from PR8 virus was used as a positive control [23]. Mice were i.n.…”
Section: Viruses With Different Perfect Mirna Target Sites Inserted Imentioning
confidence: 99%
“…LAIV platforms offer improved immunogenicity through both attenuated replication and mucosal delivery, which more closely resembles natural infection. However, the potential for LAIVs to resort to virulence has raised safety concerns (38). This is particularly concerning within livestock where, due to the potential for reassortment and creation of novel strains, only killed vaccines are recommended (9).…”
Section: Discussionmentioning
confidence: 99%